Bored with Barthes: ennui in China. Issue 2 (23rd February 2016) - Badmington, Neil
Abstract : Between 11 April and 4 May 1974, Roland Barthes visited Mao's China. Accompanying him on the trip were François Wahl and, representing Tel Quel, Julia Kristeva, Marcelin Pleynet, and Philippe Sollers. Barthes published a short, disaffected piece on the experience in Le Monde shortly after his return, but the true scale and level of his disappointment did not become apparent until 2009, when several journals that he filled during the trip were published in French as Carnets du voyage en Chine ; an English translation, Travels in China, followed in 2012. After tracing the neglected history of boredom in Barthes more generally, this essay examines the overwhelming ennui articulated in Travels in China . If Barthes is, as Steven Ungar argued many years ago, a professor of desire, I propose here that he is also a professor of boredom. What Travels in China allows us to see is the significance of Barthes's discussions of ennui and the relationship between boredom and the familiar Barthesian theme of doxa. Scholarly accounts of ennui tend to overlook Barthes or reduce him to a single line from The Pleasure of the Text, but I argue that we might correct this oversight and begin at last to read Barthes as a remarkable professor of boredom.